The Zinc-Schiff Base-Novicidin Complex as a Potential Prostate Cancer Therapy - Milosavljevic, Vedran; Haddad, Yazan; Merlos Rodrigo, Miguel Angel; Moulick, Amitava; Polanska, Hana; Hynek, David; Heger, Zbynek; Kopel, Pavel; Adam, Vojtech (PloS one, 2016)
Prostate cancer cells control energy metabolism by chelating intracellular zinc. Thus, zinc delivery has been a popular therapeutic approach for prostate cancer. Here, we propose the use of the membrane-penetrating peptide Novicidin connected to zinc-Schiff base as a carrier vehicle for the delivery of zinc to prostate cells. Mass spectrometry, electrochemistry and spectrophotometry confirmed the formation/stability of this complex and provided insight regarding the availability of zinc for complex interactions. This delivery system showed minor toxicity in normal PNT1A cells and high potency towards PC3 tumor cells. The complex preferentially penetrated PC3 tumor cells in contrast to confinement to the membranes of PNT1A. Furthermore, zinc uptake was confirmed in both cell lines. Molecular analysis was used to confirm the activation of zinc stress (e.g., ZnT-1) and apoptosis (e.g., CASP-1). Our results strongly suggest that the zinc-Schiff base-Novicidin complex has great potential as a novel anticancer drug.
Keywords: nádorové buněčné linie; Schiff Bases; Zinc; apoptóza; fluorescenční mikroskopie; Coordination Complexes; Microscopy, Fluorescence; kationické antimikrobiální peptidy; komplexní sloučeniny; Cation Transport Proteins; mužské pohlaví; nádory prostaty; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Cell Line, Tumor; Caspase 1; Antineoplastic Agents; Schiffovy báze; Gene Expression; Molecular Conformation; kaspasa 1; protinádorové látky; Humans; Prostatic Neoplasms; molekulární konformace; Antimicrobial Cationic Peptides; spektrometrie hmotnostní - ionizace laserem za účasti matrice; exprese genu; zinek; proteiny přenášející kationty; lidé; Male; Apoptosis